PROFIL KEMAMPUAN METAKOGNITIF SISWA PADA PEMBELAJARAN IPA KELAS VII DI SMPN 13 KOTA SUKABUMI - Erisa Septiyani; Billyardi Ramdhan; Aa Juhanda (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2020)
This study aimed to know the metacognitive abilities of junior high school students in Kota Sukabumi. Metacognitive abilities are the students' ability to plan, monitor, and evaluate the students' learning process. In learning science, metacognitive skills are needed such as planning, information organizing, and monitoring the understanding of learning. The research type was descriptive with a purposive sampling technique. This research was done at Junior High School of 13 Sukabumi of 2019-2020 academic year. The instruments were measured by using the Metacognitive Awareness Inventory (MAI). The data categorized into four criteria; very good, good, enough, poor, and very poor. The study shows that the criteria for the abilities of the students are 55% for poor criteria, 39% for enough criteria, and 6% (as many as 2 people) for good criteria. The conclusion of the data is metacognitive abilities of the students are still lacking, suggesting the need for improvement in the learning process both in the assessment and learning model.